2022
DOI: 10.3389/fpls.2022.842628
|View full text |Cite
|
Sign up to set email alerts
|

Agroclimatic Metrics for the Main Stone Fruit Producing Areas in Spain in Current and Future Climate Change Scenarios: Implications From an Adaptive Point of View

Abstract: Stone fruit production has enormous economic importance in Spain. Cultivation locations for these fruit species (i.e., peach, apricot, plum, and sweet cherry) cover wide and climatically diverse geographical areas within the country. Climate change is already producing an increase in average temperatures with special intensity in certain areas like the Mediterranean ones. These changes lead to a decrease in the accumulated chill, which can have a profound impact on the phenology of Prunus species like stone fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…For temperate fruit and nut trees, adequate winter chill and heat accumulation are critical requirements for satisfactory commercial production ( Gordo and Sanz, 2009 ; Cerutti et al., 2011 ; Luedeling et al., 2013 ; Darbyshire et al., 2016 ; Horikoshi et al., 2018 ; Fadon et al., 2020 ; Fernandez et al., 2020a ; del Barrio et al., 2022 ). Insufficient winter chill and increasing heat during key phenological stages can affect important physiological processes, leading to non-uniform flowering ( El Yaacoubi et al., 2014 ; Orlandi et al., 2014 ; Legave et al., 2015 ; Funes et al., 2016 ; Elloumi et al., 2024 ), delayed bud formation ( Bonhomme et al., 2005 ; El Yaacoubi et al., 2016 ; Yi et al., 2020 ; Barba-Espin et al., 2022 ), abnormal bud-break ( Bonhomme et al., 2005 ), fruit set reduction ( Hedhly et al., 2007 ; Ruiz and Egea, 2008 ; Benlloch-Gonzalez et al., 2018 ; Egea et al., 2022 ), and ultimately reduced yield potential ( Benmoussa et al., 2018 ; Moriondo et al., 2019 ; Mujahid et al., 2020 ; Fernandez et al., 2021 ). The literature reports a consistent decline in winter chill in all warm temperate climate regions around the world, which explains the high research interest in this topic.…”
Section: Discussionmentioning
confidence: 99%
“…For temperate fruit and nut trees, adequate winter chill and heat accumulation are critical requirements for satisfactory commercial production ( Gordo and Sanz, 2009 ; Cerutti et al., 2011 ; Luedeling et al., 2013 ; Darbyshire et al., 2016 ; Horikoshi et al., 2018 ; Fadon et al., 2020 ; Fernandez et al., 2020a ; del Barrio et al., 2022 ). Insufficient winter chill and increasing heat during key phenological stages can affect important physiological processes, leading to non-uniform flowering ( El Yaacoubi et al., 2014 ; Orlandi et al., 2014 ; Legave et al., 2015 ; Funes et al., 2016 ; Elloumi et al., 2024 ), delayed bud formation ( Bonhomme et al., 2005 ; El Yaacoubi et al., 2016 ; Yi et al., 2020 ; Barba-Espin et al., 2022 ), abnormal bud-break ( Bonhomme et al., 2005 ), fruit set reduction ( Hedhly et al., 2007 ; Ruiz and Egea, 2008 ; Benlloch-Gonzalez et al., 2018 ; Egea et al., 2022 ), and ultimately reduced yield potential ( Benmoussa et al., 2018 ; Moriondo et al., 2019 ; Mujahid et al., 2020 ; Fernandez et al., 2021 ). The literature reports a consistent decline in winter chill in all warm temperate climate regions around the world, which explains the high research interest in this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Spain, which recorded the most studies, is the seventh plum producer in the world and third in the European Union [28]. Plum production is of economic importance to Spain [29], as the cultivation of this fruit tree covers broad and climatically diverse regions within the country [30]. Spain is not exempted from the global effects of climate change and climate variability.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Additionally, global warming has become a new challenge for the physiology of deciduous species (Luedeling, 2012), since an increase of 3.2°C in the global average temperature is expected by the end of the 21st century, compared to the year 1960 (IPCC, 2021). This could decrease the accumulation of CH in deciduous species, affect bud break and reduce pollinator activity (Egea et al, 2022), as has been observed in cultivated apple trees in the subtropical highlands of India (Nautiyal et al, 2020). Added to this, the highland areas of the tropical Andes will be more affected by climate change than the low-lying valley areas (Fischer, Parra-Coronado et al, 2022b).…”
Section: Varieties In Colombiamentioning
confidence: 99%
“…The physiological behavior of deciduous trees in the high tropics is affected by climatic conditions since, due to their origin and adaptation in temperate zones (Erez, 2000;Fischer, 2013), the ecophysiological requirements of the species and the agronomic management of the crop must be fulfilled in a differential way (Gutiérrez-Villamil et al, 2022). In addition, climate change is a current risk for the production of deciduous fruit trees, including plum, as changes in temperature can affect their physiology, phenology and production (Egea et al, 2022). Considering the great importance and the productive and nutritious potential of the plum tree for growing and adaptation in the tropical highlands, the objective of this review was to present the current state of research in physiology adaptation and management, including aspects such as variety selection, ecophysiology, forced production management, gas exchange, flowering, pollination and fruit development of the Japanese plum.…”
Section: Introductionmentioning
confidence: 99%